Placental OLAH Levels Are Altered in Fetal Growth Restriction, Preeclampsia and Models of Placental Dysfunction - Natasha de Alwis; Sally Beard; Natalie K. Binder; Natasha Pritchard; Tu'uhevaha J. Kaitu'u-Lino; Susan P. Walker; Owen Stock; Katie Groom; Scott Petersen; Amanda Henry; Joanne M. Said; Sean Seeho; et al. (MDPI AG, 2022)
Previously, we identified elevated transcripts for the gene Oleoyl-ACP Hydrolase (OLAH) in the maternal circulation of pregnancies complicated by preterm fetal growth restriction. As placental dysfunction is central to the pathogenesis of both fetal growth restriction and preeclampsia, we aimed to investigate OLAH levels and function in the human placenta. We assessed OLAH mRNA expression (qPCR) throughout pregnancy, finding placental expression increased as gestation progressed. OLAH mRNA and protein levels (Western blot) were elevated in placental tissue from cases of preterm preeclampsia, while OLAH protein levels in placenta from growth-restricted pregnancies were comparatively reduced in the preeclamptic cohort. OLAH expression was also elevated in placental explant tissue, but not isolated primary cytotrophoblast cultured under hypoxic conditions (as models of placental dysfunction). Further, we discovered that silencing cytotrophoblast OLAH reduced the expression of pro- and anti-apoptosis genes, BAX and BCL2, placental growth gene, IGF2, and oxidative stress gene, NOX4. Collectively, these findings suggest OLAH could play a role in placental dysfunction and may be a therapeutic target for mitigating diseases associated with this vital organ. Further research is required to establish the role of OLAH in the placenta, and whether these changes may be a maternal adaptation or consequence of disease.